Validation and reliability of the translated Malay Version of the psychosocial impact of dental aesthetics questionnaire for adolescents - Wan Hassan, W.N. (2016)
Background: This study developed an oral health-related quality of life (OHRQoL) instrument specific for orthodontics for Malaysian adolescents between 12 and 17 years old by cross-cultural adaptation of the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ). Methods: The Malay PIDAQ was developed by a cross-cultural adaptation process followed by psychometric validations. After initial investigation of the conceptual suitability of the measure for our population, the PIDAQ was translated into Malay, pilot tested and back translated into English. Psychometric properties were examined across two age groups (12-14 and 15-17 year olds) for factor structure, internal consistency, reproducibility, discriminant and construct validity, and assessment of floor and ceiling effects. Results: Fit indices by confirmatory factor analysis showed good fit statistics (comparative fit index = 0.94, root-mean-square error of approximation = 0.06) and invariance across age groups. Internal consistency and reproducibility tests were satisfactory (Cronbach’s alpha = 0.78-0.91; intra-class correlations = 0.71-0.89). Significant differences in Malay PIDAQ mean scores were observed between subjects with severe malocclusion and those with slight malocclusion based on a self-rated and an investigator-rated malocclusion index, for all subscales and all age groups (p < 0.001). Construct validity of the Malay PIDAQ subscales with those with and without impact on daily activities attributed to malocclusion, those who rated themselves with excellent to poor dental appearance and those who felt they needed or did not need braces, also showed significant associations for all age groups (p < 0.001). There were no floor or ceiling effects detected. Conclusion: The study has provided initial evidence for the validity and reliability of the Malay PIDAQ to assess the impact of malocclusion on the OHRQoL of 12-17 year old Malaysian adolescents.